The Effect of Kahoot-based Team Game Tournament Type Cooperative Model and Learning Motivation on Indonesian Language Learning Outcomes - Afifah, Afifah; Atmazaki, Atmazaki (JOLLT Journal of Languages and Language Teaching, 2024)
This study aims to interpret the effect of the application of the Cooperative learning model type Team Game Tournament assisted by Kahoot application and learning motivation on learning outcomes on the material of writing official letters and personal letters of SMP Negeri 02 Gunung Talang students. This research is classified as experimental research with a population of 355 students and a sample of 64 students. Data on learning outcomes were obtained through objective question tests on the material of writing official and personal letters, while learning motivation data were obtained from distributing learning motivation questionnaires. Data analysis was conducted manually and using the IBM SPSS Statistics 27 application. Based on the results of the analysis, the Team Game Tournament type Cooperative learning model assisted by Kahoot application was proven effective in improving student learning outcomes significantly compared to the Conventional learning model. This is evidenced by tcount> ttable (df = 62; Î± = 0.05), namely 8.444> 1.66980 and Sig. (2-tailed) = 0.000 < 0.05 then H0 is rejected. These findings indicate that the application of the Team Game Tournament type Cooperative learning model assisted by the Kahoot application can significantly improve student learning outcomes. In addition, the results showed that students’ learning motivation, both high and low, did not significantly affect learning outcomes in the context of using the Cooperative learning model of Team Game Tournament type assisted by Kahoot application. The analysis also showed no significant interaction between the learning model and students’ learning motivation, with an interaction F value (FoA*B) = 0.013 and p-value = 0.908. Thus, the effectiveness of the Team Game Tournament type cooperative learning model assisted by Kahoot application was consistent across various levels of student learning motivation, both high and low. This finding indicates that the learning model is effective for all students regardless of their learning motivation level.